1998
DOI: 10.1161/01.cir.97.19.1946
|View full text |Cite
|
Sign up to set email alerts
|

Patent Foramen Ovale Is an Important Predictor of Adverse Outcome in Patients With Major Pulmonary Embolism

Abstract: Background-Right-to-left shunt through a patent foramen ovale is frequently diagnosed by contrast echocardiography and can be particularly prominent in the presence of elevated pressures in the right side of the heart. Its prognostic significance in patients with pulmonary thromboembolism, however, is unknown. Methods and Results-The present prospective study included 139 consecutive patients with major pulmonary embolism diagnosed on the basis of clinical, echocardiographic, and cardiac catheterization criter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
164
1
41

Year Published

1999
1999
2012
2012

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 369 publications
(208 citation statements)
references
References 33 publications
(29 reference statements)
2
164
1
41
Order By: Relevance
“…12 In the context of pulmonary embolism, a 5-fold increased risk for mortality or systemic emboli was found in patients with a PFO. 13 A rare and peculiar syndrome is platypnea orthodeoxia. 14 It can be seen in elderly patients who become cyanotic and dyspneic while sitting up; these problems disappear when the patients are lying down.…”
Section: Miscellaneousmentioning
confidence: 99%
“…12 In the context of pulmonary embolism, a 5-fold increased risk for mortality or systemic emboli was found in patients with a PFO. 13 A rare and peculiar syndrome is platypnea orthodeoxia. 14 It can be seen in elderly patients who become cyanotic and dyspneic while sitting up; these problems disappear when the patients are lying down.…”
Section: Miscellaneousmentioning
confidence: 99%
“…However, recent assessments suggest that persistent EV may predispose to patency of the foramen ovale [3]. While a patent foramen ovale in patients with pulmonary embolic disease is associated with a ten-fold increase in death and a five-fold increase in the risk of adverse outcomes during the hospital stay [4], the added risk of a persistent EV may increase the risk of embolic thrombosis to the left atrium and arterial circulation [3].…”
Section: Discussionmentioning
confidence: 99%
“…11 In 139 consecutive patients with PE, Konstantinides et al found that the presence of a patent foramen ovale doubles the mortality rate compared with patients with a PE and no shunt. 11 Thrombolytic therapy should be considered in patients with acute PE who have hemodynamic embarrassment or evidence of RV dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…11 In 139 consecutive patients with PE, Konstantinides et al found that the presence of a patent foramen ovale doubles the mortality rate compared with patients with a PE and no shunt. 11 Thrombolytic therapy should be considered in patients with acute PE who have hemodynamic embarrassment or evidence of RV dysfunction. [2][3][4] Nonrandomized registry data 12 have shown that thrombolytics decrease mortality when administered to hemodynamically stable patients with PE and RV dysfunction.…”
Section: Discussionmentioning
confidence: 99%